2021
DOI: 10.1002/chem.202102413
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Frameworks with Novel Catenane‐like Interlocking: Metal‐Determined Photoresponse and Uranyl Sensing

Abstract: The assembly of two tripyridinium‐tricarboxylate ligands and different metal ions leads to seven isostructural MOFs, which show novel 2D→2D supramolecular entanglement featuring catenane‐like interlocking of tricyclic cages. The MOFs show tripyridinium‐afforded and metal‐modulated photoresponsive properties. The MOFs with d10 metal centers (1‐Cd, 1‐Zn, 2‐Cd, 2‐Zn) show fast and reversible photochromism and concomitant fluorescence quenching, 1‐Ni displays slower photochromism but does not fluoresce, and 1‐Co a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Detailed structural analysis was further conducted to identify the possible transfer path for the ET process in these compounds. Previous studies have suggested that photoinduced ET in solid-state viologen compounds generally occurs through a short contact between the pyridinium moiety and an electron donor (D), for instance, N pyridinium ···D, ,, (α-C–H) pyridinium ···D, , and π pyridinium ···π D . , Typically, the appropriate N···O distance for ET is less than 4.0 Å. ,, In our study, we found that the distances between the carboxylate oxygen atoms and pyridine nitrogen atoms were 3.267–3.327 Å for 1 , 3.044–3.904 Å for 2 , 3.092–3.851 Å for 3 , and 3.204 and 3.360 Å for 4 , which locate at suitable distances for photoinduced ET (Figure ). Therefore, in this work, due to the strong hydrogen-bonding interactions together with other intermolecular interactions, the hydrogen atom in the coordinated H 2 O delocalizes and approaches the nitrogen atoms of the pyridine derivatives, which facilitates photoinduced ET from the carboxylates in the host to the pyridine derivatives, resulting in the formation of photogenerated radicals, similar to the behavior of viologen molecules.…”
Section: Resultssupporting
confidence: 49%
“…Detailed structural analysis was further conducted to identify the possible transfer path for the ET process in these compounds. Previous studies have suggested that photoinduced ET in solid-state viologen compounds generally occurs through a short contact between the pyridinium moiety and an electron donor (D), for instance, N pyridinium ···D, ,, (α-C–H) pyridinium ···D, , and π pyridinium ···π D . , Typically, the appropriate N···O distance for ET is less than 4.0 Å. ,, In our study, we found that the distances between the carboxylate oxygen atoms and pyridine nitrogen atoms were 3.267–3.327 Å for 1 , 3.044–3.904 Å for 2 , 3.092–3.851 Å for 3 , and 3.204 and 3.360 Å for 4 , which locate at suitable distances for photoinduced ET (Figure ). Therefore, in this work, due to the strong hydrogen-bonding interactions together with other intermolecular interactions, the hydrogen atom in the coordinated H 2 O delocalizes and approaches the nitrogen atoms of the pyridine derivatives, which facilitates photoinduced ET from the carboxylates in the host to the pyridine derivatives, resulting in the formation of photogenerated radicals, similar to the behavior of viologen molecules.…”
Section: Resultssupporting
confidence: 49%
“…Chen and Wang obtained a series of 2D isomorphous MOFs [M(HBTC)(BMIOPE)·DMF·H 2 O] n (M = Zn, Zn 0.7 Co 0.3 , Zn 0.5 Co 0.5 , Zn 0.3 Co 0.7 , Co, BMIOPE = 4,4′-bis(2-methylimidazol-1-yl)diphenyl ether, H 3 BTC = 1,3,5-benzenetricarboxylic acid) to discuss the optical detection of UO 2 2+ in an aqueous solution [ 93 ]. Seven isostructural MOFs indicating novel 2D→2D supramolecular entanglement featuring catenane-like interlocking of tricyclic cages by the assembly of two tripyridinium-tricarboxylate ligands and different metal ions were reported by Guo et al, as shown in Figure 12 a [ 94 ]. The tripyridinium-afforded and metal-modulated photoresponsive properties of Cd-MOF allow it to be used as a potential fluorescence sensor for sensitive and selective detection of UO 2 2+ in water, as shown in Figure 12 b.…”
Section: Lmofs For Hazardous Materials Detectingmentioning
confidence: 99%
“…[145][146][147] Catenanes are at the forefront of this field to construct artificial molecular machines and take advantage of the dynamics of interlocked structures in polymers, metal/covalent-organic frameworks (M/COFs), and other materials. [148][149][150][151][152] Their research has resulted in significant advancements that have significance for various scientific fields, from biology to soft matter physics, as well as supramolecular chemistry. 153 Like rotaxanes, catenanes have a naming system where the term is preceded by square brackets denoting the number of macrocycles that make up a catenane.…”
Section: Chemical/redox Switching In Catenanesmentioning
confidence: 99%